2020
DOI: 10.1093/trstmh/traa130
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study to evaluate depression and quality of life among patients with lymphoedema due to podoconiosis, lymphatic filariasis and leprosy

Abstract: Background Podoconiosis, lymphatic filariasis (LF) and leprosy are neglected tropical diseases (NTDs) that cause lymphoedema. When left untreated, they lead to substantial disability. This study determined the quality of life (QOL) and depression associated with lymphoedema in patients with podoconiosis, LF and leprosy. The study was conducted in northwestern Ethiopia. Methods This baseline cross-sectional study, nested withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…1,20,21 People living with podoconiosis are disproportionately severely stigmatized through exclusion from schools, local meetings, churches, and mosques. They are often denied marriage with uninfected individuals, 19,[22][23][24] have a reduced quality of life, 25,26 lower productivity, and increased rates of depression. [27][28][29] Several studies have identified individual and environmental correlates thought to be associated with the development of podoconiosis.…”
Section: Introductionmentioning
confidence: 99%
“…1,20,21 People living with podoconiosis are disproportionately severely stigmatized through exclusion from schools, local meetings, churches, and mosques. They are often denied marriage with uninfected individuals, 19,[22][23][24] have a reduced quality of life, 25,26 lower productivity, and increased rates of depression. [27][28][29] Several studies have identified individual and environmental correlates thought to be associated with the development of podoconiosis.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Causing pain, disability and social isolation, these conditions significantly impair health-related quality of life, mental health and economic activity in the people they affect. 2–6 …”
Section: Introductionmentioning
confidence: 99%
“…As highly stigmatized conditions, they have a huge impact on the lives of the people they affected, causing physical disability, reducing economic productivity, and impairing mental well-being. [1][2][3][4][5][6][7] Morbidity management and disability prevention (MMDP) services have been shown to be effective in mitigating the impacts of all three of these diseases. Several studies, including randomized controlled trials, have demonstrated that encouraging simple self-care measures to promote foot hygiene can reduce limb swelling and improve quality-of-life.…”
Section: Introductionmentioning
confidence: 99%
“…As highly stigmatized conditions, they have a huge impact on the lives of the people they affect, causing physical disability, reducing economic productivity, and impairing mental well-being. 1 7 …”
Section: Introductionmentioning
confidence: 99%